Relationship between Supervision and End of Life Care Documentation in Inpatient Room at Hospital in South Jakarta - Krisna Yetti Malawat; Azis Fahruji; Kuntarti (International Journal of Nursing and Health Services (IJNHS), 2020)
Introduction: Patients treated in hospitals with end-of-life patients are more likely to be in the intensive care room than patients treated in the standard care room because, if there is an end of life, they are moved to the inpatient room required the implementation of supervision on documenting the end of life care, so that the quality of service improves. Objective: To identify the relationship between supervision implementation and EoLC documentation in the intensive care room. Method: Cross-sectional design was used. Univariate, bivariate, and multivariate were used to analyze. Results: The mean age was 35.68 ± 7.232 years, tenure 12.12 ± 7.623 years, 78.3% women, Nursing Diploma 64.2%, implementing nurses 95.8%, PNS 63.2%, PK2 44.8 % and have attended 55.7% training. The average supervision implementation was 51.20%, the technical dimension was 68.30%, the principal was 66.73%, the model was 64.47%, and the routine activities were 51.82%, and documentation was 74.17% EoLC. There is a significant relationship between supervision (techniques, principles, routine activities, and supervision models) with EoLC documentation. The dominant dimension of supervision is the supervision model with medium strength and a positive direction. There are three variables: gender, position, and supervision model can increase EoLC documentation by 27.8% (R2 = 0.278), while other variables can increase the rest. EoLC documentation equation = 75,479 + 3,763 Gender + (-8,366) Position + 2,108 Supervision Model. Conclusion: The nursing sector creates an SPO program to carry out supervision and documentation of EoLC to create effectiveness in nursing services that have an impact on patient quality and safety